Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1093/geronb/55.5.s298
|View full text |Cite
|
Sign up to set email alerts
|

Disability Trends Among Elderly Persons and Implications for the Future

Abstract: Objectives. This article used a new data source to examine the issue of disability trends among elderly persons and examined the potential implications of these trends on future health and long-term care needs.Methods. We used the 1992-1996 Medicare Current Beneficiary Survey to examine time trends in rates of activities of daily living and instrumental activities of daily living disability and physical limitation among Medicare beneficiaries aged 65 and over. We used multinomial logit and least squares regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
133
0
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(153 citation statements)
references
References 22 publications
13
133
0
4
Order By: Relevance
“…Analyzes suggest that future changes in education levels would continue to contribute to improving the functionality of the populations. 31 A U.S. study showed by calculating DFLE between 1970 and 1990 that the compression of morbidity began with individuals with more years of education. 32 A study from Austria about educational disparity trends showed that, among women, there is a significant increase of the difference in healthy life expectancy between people from middle-and low-education backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzes suggest that future changes in education levels would continue to contribute to improving the functionality of the populations. 31 A U.S. study showed by calculating DFLE between 1970 and 1990 that the compression of morbidity began with individuals with more years of education. 32 A study from Austria about educational disparity trends showed that, among women, there is a significant increase of the difference in healthy life expectancy between people from middle-and low-education backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Life expectancies are increasing in general and evidence suggests that these additional years are being lived in good health [40,41]. In order to use these results to more accurately model future data we need to consider increases and convergences in life expectancies.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, según el mismo estudio, en el caso de España la prevalencia en este grupo de edad es de un 35%, cifra semejante a la del presente estudio. Cotas similares se han encontrado en estudios realizados en Estados Unidos 1,[60][61][62] . Los datos del estudio europeo SHARE sitúan a España como el país con una mayor prevalencia de discapacidad, junto con Grecia y Francia (29% y 28% respectivamente).…”
Section: Discussionunclassified
“…Si bien la discapacidad no es una consecuencia inevitable del envejecimiento, las situaciones de fragilidad son crecientes a edades avanzadas, pudiendo desembocar en pérdida de autonomía y dependencia [1][2][3][4][5] . El deterioro funcional y cognitivo que se puede alcanzar en momentos avanzados de la vejez no se asocia tan sólo con el envejecimiento, sino también con el estilo de vida y las características del entorno del individuo.…”
Section: Introductionunclassified
See 1 more Smart Citation